Implementation of Lean Management in Reducing Waste and Increasing Productivity of Intercity Bus Transportation RAPI - Lubis, Muhammad Syahrozi; Nurlaila; Nurbaiti (Jurnal Manajemen Bisnis, 2026)
This study analyzes the application of management in improving the operational effectiveness of intercity bus transportation at PT. NEAT. Management plays a crucial role in managing resources through the Planning, Organizing, Actuating, and Controlling (POAC) functions so that operational activities can run efficiently and productively. However, public transportation still frequently faces obstacles in the form of waste and inefficiency that impact the decline in service quality and customer satisfaction. To address these issues, this study uses the Lean Management approach, a management method that focuses on eliminating non-value-added activities to increase productivity. The study was conducted using a qualitative descriptive method through interviews and observations. This research method also involves identifying improvements to process flow and measuring performance before and after improvements. Academically, this research is based on the concept of operational productivity which emphasizes the elimination of non-value added activities to increase service efficiency. The results show that the main waste at PT. RAPI is waiting time and defects (bus damage), which causes increased operational costs and a decrease in the number of passengers served. Improvements that have been made include more efficient fleet scheduling, planned bus maintenance, and digitalization of administration. The implications of this study emphasize the importance of improving the quality of human resources, both through skills training, increased work discipline, and strengthened employee responsibility, so that the implementation of Lean Management can run more optimally and sustainably.